Optimizing the Security of the Indonesian State through Strengthening International Cooperation between Indonesia and Malaysia in the Land Border - Edward Yohanes Yohanes Partoga; Joko Setiyono (Jurnal Hukum Prasada, 2020)
Indonesia is an island nation consisting of land and sea areas. The constitutional foundation of Indonesia has regulated that the Unitary State of the Republic of Indonesia is an archipelagic nation characterized by an archipelago with territories whose boundaries and rights are determined by law. This is as regulated in Article 25 (A) of the 1945 Constitution of the Republic of Indonesia. The purpose of this research is the application of international cooperation between Indonesia and Malaysia in the land border area and the driving and inhibiting factors for international cooperation between Indonesia and Malaysia in the land border area. . The approach method used in this study is the Legal Research approach method. Implementation of International Cooperation between Indonesia and Malaysia in the Border Area, The application of international cooperation between Indonesia and Malaysia proves that there is an international interaction as a country that is close together in terms of geographical location. Drivers of factors and obstacles to international cooperation between Indonesia and Malaysia in the border of land areas. The role of the central, provincial and district / city government in developing border areas needs to be done appropriately and emphasizes three main points, namely: Regulators, Executors and Government facilitators as regulators are obliged to encourage structuring the rules that exist in the development and utilization of border areas in the decision making effort. Conclusion The application of the agreement made between Indonesia and Malaysia is a strategic step for the two countries to mutually reinforce sovereignty in the country's security efforts